Research Progress on the Role of Vitamin D in Autism Spectrum Disorder - Wang, Jing; Huang, Haoyu; Liu, Chunming; Zhang, Yangping; Wang, Wenjuan; Zou, Zhuo; Yang, Lei; He, Xuemei; Wu, Jinting; Ma, Jing; Liu, Yun (Frontiers in Behavioral Neuroscience, 2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that can lead to serious social behavioral problems, mainly manifested as social communication and interaction disorders, narrow interests and repetitive stereotyped behaviors. In recent years, the prevalence of ASD is increasing year by year, and it has developed from a rare disease to a high incidence of childhood developmental disorders. The pathogenesis of ASD is considered to be the interaction of genetic and environmental factors. There is increasing evidence that vitamin D deficiency in pregnancy and early childhood can lead to the occurrence of ASD. Studies have shown that vitamin D intervention can significantly improve the symptoms of ASD, but the mechanism by which vitamin D improves the clinical symptoms of ASD is still unclear. Therefore, exploring the neuroprotective mechanism of vitamin D on ASD is a huge challenge and problem faced by current basic and clinical research, which is of great significance for clinical promotion and optimization of vitamin D in the treatment of ASD. In order to further clarify the relationship between vitamin D and ASD, this review summarizes the correlation between vitamin D expression level and ASD, the effects of vitamin D supplementation on ASD, the possible mechanism of vitamin D involved in ASD and the insights from ASD animal models.